Anatomy of a Merger: The Causes and Effects of Mergers and Acquisitions. - Niden, Cathy M.; Post, Alexandra M. (Journal of Finance, 1994)
Part 1 Why firms merge: recent history of M&A waves M&A personae creative financing - the new techniques corporate control and expansion via M taxation, deregulation and antitrust legislation merger waves - a cyclical dynamic approach. Part 2 Checklist review of the literature: a checklist of causes - why firms merge a checklist of effects - post-acquisition outcomes a checklist of success and failure factors.